Insights into the Development of the Adult Leydig Cell Lineage from Stem Leydig Cells - Ye, Leping; Li, Xiaoheng; Li, Linxi; Chen, Haolin; Ge, Ren-Shan (Frontiers in Physiology, 2017)
Adult Leydig cells (ALCs) are the steroidogenic cells in the testes that produce testosterone. ALCs develop postnatally from a pool of stem cells, referred to as stem Leydig cells (SLCs). SLCs are spindle-shaped cells that lack steroidogenic cell markers, including luteinizing hormone (LH) receptor and 3β-hydroxysteroid dehydrogenase. The commitment of SLCs into the progenitor Leydig cells (PLCs), the first stage in the lineage, requires growth factors, including Dessert Hedgehog (DHH) and platelet-derived growth factor-AA. PLCs are still spindle-shaped, but become steroidogenic and produce mainly androsterone. The next transition in the lineage is from PLC to the immature Leydig cell (ILC). This transition requires LH, DHH, and androgen. ILCs are ovoid cells that are competent for producing a different form of androgen, androstanediol. The final stage in the developmental lineage is ALC. The transition to ALC involves the reduced expression of 5α-reductase 1, a step that is necessory to makes the cells to produce testosterone as the final product. The transitions along the Leydig cell lineage are associated with the progressive down-regulation of the proliferative activity, and the up-regulation of steroidogenic capacity, with each step requiring unique regulatory signaling.